Risk assessment of obstructive sleep apnea syndrome and other sleep disorders in multiple sclerosis patients - GÜNAL, DİLEK; VURAL, EZGİ; SÜNTER, GÜLİN; AĞAN YILDIRIM, KADRİYE (ELSEVIER, 2021)
Background: The aim of the present study was to determine the possible risk of OSAS in patients with MS through the STOP-BANG questionnaire, and to confirm the pre-diagnosis of OSAS by recording polysomnographic investigation in individuals with high risk. In addition, the relationship between OSAS risk and fatigue, sleepiness, depression, and disability status will be examined. Methods: Totally 97 patients with multiple sclerosis including 36 males and 61 females with an age average of 39.92 +/- 9.11 years. All participants completed the following questionnaires: STOP-Bang, Fatigue Severity Scale (FSS), Epworth sleepiness scale (ESS), Beck Depression Inventory (BDI); disability status of the participants was assessed by Expanded Disability Status Scale (EDSS). Polysomnographic sleep record was applied to the patients with high risk of OSAS according to STOP-BANG test scores. Results: The STOP_BANG questionnaire revealed that 24.7% of the patients were screened as high risk for OSA. Approximately 11.3% of the patients were detected positive for OSAS based on PSG recording. Comparison of MS patients with high risk of OSA with others suggested a significant difference in terms of the age (p = 0.01). ESS positive scores were significantly correlated with positive STOP BANG outcomes (p < 0.001). ESS positive scores were negatively correlated with positive PSG outcomes. Conclusion: The prevalence of OSAS in MS patients based on questionnaire and PSG was found consistent with literature. Similar to the general population, increasing age was found as a risk factor for OSAS in patients with MS. STOP-BANG test may not be an adequate test to diagnose OSAS, especially in MS patients with high fatigue scores.
Keywords: Obstructive sleep apnea syndrome; Multiple sclerosis; STOP-BANG questionnaire; Polysomnography; Depression; QUALITY-OF-LIFE; STOP-BANG; FATIGUE; PREVALENCE; IMPACT; QUESTIONNAIRE; EPIDEMIOLOGY; DIAGNOSIS